A good sketch is better than a long speech: evaluate delinquency risk through real-time video analysis - Chang, Xiangyu; Dai, Lili; Feng, Lingbing; Han, Jianlei; Shi, Jing; Zhang, Bohui (Review of Finance, 2025)
Abstract This article proposes an innovative method to assess borrowers’ creditworthiness in consumer credit markets by conducting machine-learning-based analyses on real-time video information that records borrowers’ behavior during the loan application process. We find that the extent of borrowers’ micro-facial expressions of happiness is negatively associated with loan delinquency likelihood, while the degree of fear expressions is positively associated with delinquency risk. These results are consistent with two economic channels relating to the adequacy and uncertainty of borrowers’ future income, drawn from the extant psychology and economics literature. Our study provides important practical implications for fintech lenders and policymakers.